THE EFFECTIVENESS OF INFORMATION GAP METHOD TO TEACH SPEAKING VIEWED FROM STUDENTS’ CREATIVITY - Herdawan, Deri (Universitas Islam Negeri Raden Intan Lampung, 2015)
The objective of this experimental research is to reveal the effectiveness of Information Gap Method to teach speaking to high school students in Tumijajar. This study involves three variables. Two independent variables are teaching methods (Information Gap Method and Audio Lingual Method) and students’ level of creativity. The dependent variable is speaking skill. The research examines the effect of the two independent variables on the dependent variable. The samples were two classes which consist of 30 students of class X2 as the experimental class and 30 students of class X4 as the control class. The instruments used to gather data in this research cover speaking test and creativity test. The data were analyzed using ANOVA and Tukey test. From the analysis, it reveals that: (1) Information Gap Method is more effective than Audio Lingual Method to teach speaking; (2) the students having high level of creativity have better speaking skill than those having low level of creativity; and (3) there is an interaction between teaching methods and the students’ level of creativity to teach speaking. While Information Gap Method is effective to teach speaking, to implement the methods, a teacher must consider about the students’ level of creativity.